2023
DOI: 10.2351/7.0000904
|View full text |Cite
|
Sign up to set email alerts
|

Powder catchment efficiency in laser cladding (directed energy deposition). An investigation into standard laser cladding and the ABA cladding technique

Abstract: This paper investigates the efficiency of powder catchment in blown powder laser cladding (a directed energy deposition technique). A comparison is made between standard “track by overlapping track” cladding (“AAA” cladding) and “ABA” cladding, where the gaps left between an initial set of widely spaced tracks (“A” tracks), are filled in by subsequent “B” tracks. In both these techniques, the melt pool surface is the collection area for the cladding powder, and the shape of this pool can be affected by several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…On the left, the melt front substantially lags the powder stream in every case. Earlier work by the present authors 7 suggested that this is due to the laser interacting with the curved, sloping "shoulder" of the previous track, which means that the projected beam has a lower energy density (also, other factors such as angular dependence of absorption need to be taken into account).…”
Section: B "Aaa" Cladding With Different Intertrack Spacingsmentioning
confidence: 74%
See 3 more Smart Citations
“…On the left, the melt front substantially lags the powder stream in every case. Earlier work by the present authors 7 suggested that this is due to the laser interacting with the curved, sloping "shoulder" of the previous track, which means that the projected beam has a lower energy density (also, other factors such as angular dependence of absorption need to be taken into account).…”
Section: B "Aaa" Cladding With Different Intertrack Spacingsmentioning
confidence: 74%
“…From the software analysis of the HSI video, it was possible to identify the mass of incoming powder entering the melt pool as a percentage of the total powder feed rate, and this can be expressed as the powder catchment efficiency. 7 Figures for powder catchment efficiency can also be calculated by measuring the cross section of the clad tracks and, thus, the mass per unit time laid down in the clad layer. Both sets of results are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, there are many surface modification technologies, such as ion implantation technology [10], thermal spraying technology [11], and laser cladding technology [12]. Ion implantation technology requires high experimental conditions and needs to be carried out under high vacuum, which is not easy to operate.…”
Section: Introductionmentioning
confidence: 99%